2,4-D herbicide toxicity on Beta vulgaris L. (beet) seed germination - França, Roberta Sorhaia Samayara Rocha Sousa de; Possenti, Jean Carlo; Santana, Asser Botelho (Brazilian Journal of Science, 2023)
The herbicide 2,4-D (2,4-dichlorophenoxyacetic acid) stands out as one of the most sold active ingredients (AI) in Brazil due to its low price. 2,4-D is part of the class of herbicides that play a key role in controlling weeds in agriculture worldwide, it has toxicological classification I and is considered extremely toxic. Beetroot (Beta vulgaris) is a tuberous root originating in the Middle East that has been spreading throughout the world, from the Americas to Europe and Asia to Oceania. It is a functional ingredient in the development of several meals in Brazilian cuisine, and also represents a highly renewable and low-cost source of nutrients. The present work evaluated the effect of the toxicity of the 2,4-D herbicide on the germination of B. vulgaris seeds. The experiment followed a completely randomized design, using a control and three concentrations of the 2,4-D herbicide (0.04; 0.08 and 0.12 mg mL-1). Germinative paper was used as substrate, placed in a germinator box. The count of germinated seeds was performed at 7 and 14 days. Beet germination was compromised, with only the control presenting an effective germination rate. In the germination boxes containing doses-responses of 2,4-D the seeds showed atrophies and fungi, with low development below 10%, only the control showed healthy germination with 65% of germination rate. 2,4 D was shown to be toxic to Beta vulgaris seeds in the usual concentrations in this study.